2000
DOI: 10.1046/j.1365-2257.2000.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemic small cell variant anaplastic large cell lymphoma during pregnancy

Abstract: The history of a 28-year-old woman with anaplastic large cell lymphoma (ALCL) in the first trimester of her pregnancy is reported. Investigations allowed to diagnose a T-cell CD30 positive ALCL, which appearance is rare during pregnancy. Moreover, the atypical lymphoid cells were found in the peripheral blood and were predominantly small to medium sized with nuclear irregularities and cytoplasmic azurophilic granules, which allowed the hypothesis of leukaemic presentation of a small cell variant ALCL. A varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…As previously described in literature (Kinney et al , ; Bayle et al , ; Lesesve et al , ), most cases in our series (6/9) included the presence of a small cell variant component. The presence of a small cell component, which may be recognized in 20–25% of ALK+ ALCL, has already been shown to be associated with a worse outcome (Lamant et al , ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As previously described in literature (Kinney et al , ; Bayle et al , ; Lesesve et al , ), most cases in our series (6/9) included the presence of a small cell variant component. The presence of a small cell component, which may be recognized in 20–25% of ALK+ ALCL, has already been shown to be associated with a worse outcome (Lamant et al , ).…”
Section: Discussionsupporting
confidence: 69%
“…Bone marrow involvement in anaplastic large cell lymphoma (ALCL) is detected in about 10–14% of cases using standard analyses(Le Deley et al , ; Brugieres et al , ), but its detection increases to 30% following staining for CD30+, epithelial membrane antigen (EMA) and/or anaplastic lymphoma kinase (ALK) on bone marrow biopsy specimens (Fraga et al , ) and reaches 50% at diagnosis with techniques such as qualitative or quantitative polymerase chain reaction (PCR) for NPM1‐ALK , designed to detect minimal disseminated disease (Mussolin et al , ; Damm‐Welk et al , ,b). On the contrary, massive bone marrow involvement is rare and only a few cases of ALCL with leukaemic presentation have previously been published in children and adults (Bayle et al , ; Lesesve et al , ; Onciu et al , ; Grewal et al , ; Takahashi et al , ; Nguyen et al , ; Gadage et al , ; Kolenova et al , ; He & Viswanatha, ; Imamura et al , ). Although the 2‐year overall survival rate is about 90% in ALK‐positive ALCL (Brugieres et al , ), the prognosis of leukaemic ALCL seems to be unfavorable (Bayle et al , ; Onciu et al , ; Grewal et al , ; Takahashi et al , ; Nguyen et al , ; Gadage et al , ).…”
mentioning
confidence: 99%
“…Indeed, involvement of peripheral blood is rare in ALCL, whereas the small-cell variant, which represents only 8% (31/410) of ALCL (G Delsol, personal observations, 2003), may be more frequently associated with a leukemic phase. 5,[19][20][21][22][23] With the exception of 3 cases reported by Kinney et al, 5 the blood smears show predominantly small-to medium-sized lymphocytes with nuclear irregularities and basophilic cytoplasm. However, these cells may be extremely rare and are easily overlooked on superficial examination as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Lesesve et al 9 reported ALCL with leukaemic presentation and bone marrow involvement during the patient’s first trimester of pregnancy. In this case, therapeutic abortion was done followed by chemotherapy with CHOP.…”
Section: Discussionmentioning
confidence: 99%